The efficacy and safety of electroacupuncture against urinary incontinence after stroke: A protocol for systematic review and meta analysis. Issue 38 (18th September 2020) - Wang, Peng; Shi, Jiyuan; Zhao, Liang; Li, Mengmeng; Jiao, Jiawei; Li, LingYun; Tian, Jinhui; Wang, Shiguang; Zhang, Shanfeng
Abstract: Background: Urinary incontinence (UI) is still a persistent challenge in many stroke survivors, affecting the quality of life and emotional being of these individuals. Numerous studies have demonstrated the curative effect of electroacupuncture on post-stroke incontinence, however they were mired with questionable quality and inconsistencies in safety and efficacy. Therefore, the main objective of this meta-analysis is to provide a comprehensive evaluation of the efficacy and safety of electroacupuncture against urinary incontinence after stroke, with a view of providing more reliable evidence-based solutions for UI. Methods: A systematic literature search will be conducted using PubMed, EMBASE, the Cochrane Central Register of Controlled Trials, Web of Science, and 4 Chinese databases from inception to June 2020 to identify randomized control trials that report on electroacupuncture against urinary incontinence after stroke. Two reviewers will independently identify eligible studies and extract data. The risk of bias of the included randomized control trials will be evaluated according to the Cochrane tool. Risk ratio and 95% confidence intervals will be used to estimate the efficacy of treatment, . and the grading of recommendations, assessment, development, and evaluation approach to rate the certainty of evidence. The statistical heterogeneity will be evaluated by Cochran's Q and the I 2 . Data will be analyzed using Stata software (Version 13.0, Stata Corp, College Station, TX, USA). Results: This study will provide a comprehensive evaluation of the efficacy and safety of electroacupuncture against UI after stroke, with a view of providing more reliable evidence-based solutions for UI. Ethics and dissemination: This work synthesises evidence from previously published studies and does not require ethics review or approval. A manuscript describing the findings will be submitted for publication in a peer-reviewed scientific journal. INPLASY registration number: INPLASY202050073